(untitled) - Prof. Dr. Judith Brockmann, Kassel; Prof. Dr. Janique Brüning, Kiel; Prof. Dr. Jan-Hendrik Dietrich, Berlin/München; Prof. Dr. Ingke Goeckenjan, Bochum; Prof. Dr. Urs Kramer, Passau; Prof. Dr. Eva Julia Lohse, Bayreuth; Prof. Dr. Arne Pilniok, Bielefeld; Prof. Dr. Christoph Schärtl, Heidelberg; Dr. Mareike Schmidt, Halle (Saale); Prof. Dr. Dr. Patricia Wiater, Erlangen (ZDRW Zeitschrift für Didaktik der Rechtswissenschaft, 2023)
The journal “Zeitschrift für Didaktik der Rechtswissenschaft (ZDRW)” is a journalistic forum for all aspects of the academic discourse about the teaching and learning of the law and legal studies. It opens and consolidates the perspective of research with regard to teaching and thus contributes new knowledge to the debate about legal studies and university didactics. ZDRW thus forges links between general university didactics, specialized legal didactics and legal studies. Horizons are thus broadened on both sides and different perspectives enabled with regard to teaching and learning the law. This signifies an interdisciplinary approach since in addition to legal studies, other disciplines are called on to contribute their own knowledge on teaching and learning processes. These include general higher education didactics, psychology, neurosciences and educational science, sociology and other specialized higher education didactics able to contribute towards specialized teaching in legal studies. ZDRW addresses all phases and aspects of legal education, providing general assistance for the improvement of both teaching and learning. To this end, apart from academic articles, a practical teaching forum is planned which will present ideas and discussions of detailed concepts for events and courses of study as well as individual didactical methods, thus providing impulses and points of connection for the individual teaching activities of our readers at various levels. Website: www.zdrw.nomos.de